LEGALITAS PENERAPAN CENTRAL BANK DIGITAL CURRENCY (CBDC) DI INDONESIA - Rafli Fadilah Muhammad (Magister Hukum Universitas Semarang, 2023)
This research aims to discuss the legality of implementing Central Bank Digital Currency (CBDC) in Indonesia after the enactment of the P2SK Act. This study has the background that the plan to implement CBDC is related to the presence of crypto digital currencies that potentially replace the official currency, the rupiah. In implementing CBDC, a strong legal basis is necessary, and the P2SK Act is seen as a sufficient legal basis. This research is important because without a strong legal basis, the issuance of digital rupiah or CBDC could face obstacles or challenges in the future, both from legal and political perspectives. The method of this study is normative juridical where data is collected from secondary sources or literature related to the researched issue using an approach of legislative regulations and a comparative approach. The results of this research show that the regulation of the P2SK Act has provided a legal basis for the issuance of digital rupiah or CBDC, but it is not enough as further regulations are needed, especially concerning technical aspects, which can be regulated by the Central Bank Regulations.